EXPRESSION OF NITROGEN TRANSPORTER GENES IN LEAVES OF WHEAT (Triticum aestivum L.) AND FIELD PERFORMANCES UNDER ORGANIC CONDITIONS - Merve Bayhan; Remzi Özkan; Mehmet Yildirim; Behcet Inal (Journal of Animal and Plant Sciences, 2024)
This study aimed to investigate the expression patterns of nitrogen transporter genes in wheat (Triticum aestivum L.) grown in organic farming systems. Expression profiling of these genes will provide valuable insights into the molecular mechanisms involved in nitrogen uptake and transport in wheat plants. In addition, the agronomic responses of the wheat genotypes were evaluated under organic conditions. This will help in the creation of genotypes that support effective nitrogen use in organic farming systems. The study showed that the nitrate transporter gene family member TaNRT2.1 exhibited the highest expression level. The Alada cultivar performed well in terms of yield under field conditions and showed the highest expression levels of TaNRT2.1, NRT2.1, and TaGS1. The 6DZT-03-01 genotype had the highest expression levels of NPF6.3 and AMT2.1. Alada, YE-4, and YE-31 were identified as the most suitable genotypes for organic farming. Several genes, including TaNRT2.1, were more highly expressed in the high-yielding genotype, Alada, than in the other genotypes. This suggested that nitrate and ammonium transporters play an important role in determining how different genotypes of wheat take in nitrogen. Further research is needed to understand the complex mechanisms that contribute to genotypic variation in nitrogen uptake in wheat. To fully understand the genetic basis of nitrogen uptake in wheat and to develop ways to improve nutrient management in organic farming systems, the expression levels of other genes involved in nitrogen metabolism should also be examined.
Keywords: Bread wheat; Yield; Gene expression; Nitrogen transporter genes; qRT-PCR